International Migration of Couples - Martin Junge; Martin D. Munk; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2014)
We present a theory on migration of dual-earner couples, and test it in the context of international migration. Our model predicts that the probability that a couple emigrates increases in the earnings of the primary earner. The effect of the earnings of the secondary earner may go either way. The empirical results for dual earner couples are in line with the theory. Primary earners in couples are more strongly self-selected with respect to their income than singles, a novel result that runs against the intuition that family ties weaken self-selection. Secondary earners in couples are more weakly self-selected than singles.
Keywords: F22; J12; J16; J24; 330; international migration; family migration; education; gender differences; dual-earner couples